Efeito da aplicação de herbicidas em pré-emergência e de glyphosate em pós-emergência,sobre a cultura da soja em solo compactado e não compactado - Biffe, Denis Fernando (2012)
The effects of glyphosate on soybeans is currently a topic that has been the subject of several studies, since nutritional aspects, biomass production, photosynthetic rate, diseases and phytotoxicity, however, little has been reported in the literature about the direct effects of its application on crop yield. In addition, existing studies dealing with glyphosate as a single factor within a production system, which is governed by several variables, such as the condition of the soil where the crop develops. Also, the intensive using of a single herbicide allows the selection of resistant or tolerant weeds, this way, it is necessary handle with auxiliary control alternatives, such as pre-emergent herbicides.This work aimed to perform a study correlating the impacts of glyphosate, soil density and pre-emergent herbicides on the development and soybean yield. The results indicated that glyphosate affects the photosynthetic rate, the development of root and shoot, as well as, the soybean yield and it was watched more intensive effects with the increasing soil density. Soil densities greater than 1.25 g dm-3, as the pre-emergent herbicides when applied to compacted soil, affect the grain yield of soybean.